2008
DOI: 10.1007/s00228-008-0505-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired heart rate variability and altered cardiac sympathovagal balance after antidepressant overdose

Abstract: Antidepressant overdose is associated with impaired heart rate variability in a pattern consistent with excess cardiac sympathetic activity. Further work is required to establish the significance of these findings and to explore whether the impairment of heart rate variability may be used to predict the development of arrhythmia in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Regarding TCA intoxication, antidepressant drugs are among the most common means of attempting suicide, and they are a serious risk factor for arrhythmias. Numerous studies have been performed to determine the development, type, and the severity of arrhythmia, and no standard indicator has yet been found [20]. It has been shown that HRV is markedly suppressed after imipramine and amitriptyline intake, and even if the EGC is normal, there is an association between the development of ventricular arrhythmia and increased LF/HF ratios [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding TCA intoxication, antidepressant drugs are among the most common means of attempting suicide, and they are a serious risk factor for arrhythmias. Numerous studies have been performed to determine the development, type, and the severity of arrhythmia, and no standard indicator has yet been found [20]. It has been shown that HRV is markedly suppressed after imipramine and amitriptyline intake, and even if the EGC is normal, there is an association between the development of ventricular arrhythmia and increased LF/HF ratios [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis showed that the therapeutic use of TCAs caused a considerable decrease in HRV [19]. There have been analyses showing HRV changes due to TCA-related poisoning in adults, and differences in HRV have been suggested to be predictors for ventricular arrhythmias in an adult patient [20, 21]. TCAs can be ingested accidentally or voluntarily by children or therapeutic mistakes can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Tricyclic antidepressants are capable of blocking alpha-adrenergic receptors, and this may lower systemic vascular resistance and result in hypotension, or orthostatic hypotension 35. High tricyclic doses increase sympathetic and decrease parasympathetic influence on heart rate variability 36. Tricyclic antidepressants also inhibit sodium channel conductance, so that phase 0 cardiac depolarization is delayed 37.…”
Section: Pharmacological Mechanisms Responsible For Cardiovascular Efmentioning
confidence: 99%
“…(1-4) However, little research has examined the association between HRV and acute poisoning, except for antidepressant overdoses. (5,6) Many parameters used to quantify HRV have been introduced and are categorized into time domain, frequency domain, and nonlinear parameters. Table 1 summarizes HRV parameters with a brief description of each.…”
Section: Introductionmentioning
confidence: 99%